Meningkatkan Hasil Belajar IPA Melalui Model Pembelajaran Example Non Example - Saridini Telaumbanua (JURNAL GLOBAL EDUKASI, 2020)
Abstract. This research aims to improve and enhance the quality and cognitive learning outcomes of students in science subjects semester 2 Class VIII SMP Negeri 6 Gunungsitoli 2017/2018 Academic Year through the application of example non example cooperative learning. This type of research is Classroom Action Research. Based on the results of research conducted by researchers on the application of the example non example learning model to improve the quality and cognitive learning outcomes of students in second semester science subjects Class VIII SMP Negeri 6 Gunungsitoli academic year 2017/2018 it can be concluded that through the results of the observation sheet in the first cycle obtained an average percentage of the implementation of learning activities of teacher respondents reached 65.38% and the results of the average percentage of learning quality questionnaires reached 61.82% and categorized as sufficient. In cycle II, the average percentage of the implementation of learning activities of teacher respondents reached 81.73% and the average results of the learning quality questionnaire reached 79.65% and categorized as good. Keywords: example non example, image media Abstrak: Tujuan penelitian ini untuk meningkatkan kualitas dan hasil belajar kognitif siswa pada mata pelajaran IPA semester 2 Kelas VIII SMP Negeri 6 Gunungsitoli Tahun Pembelajaran 2017/2018 melalui penerapan pembelajaran kooperatif tipe example non example. Jenis penelitian ini adalah Penelitian Tindakan Kelas (Classroom Action Research). Berdasarkan hasil penelitian yang telah dilaksanakan oleh peneliti tentang penerapan model pembelajaran example non example untuk meningkatkan kualitas dan hasil belajar kognitif siswa pada mata pelajaran IPA semester 2 Kelas VIII SMP Negeri 6 Gunungsitoli Tahun Pembelajaran 2017/2018 dapat disimpulkan bahwa melalui hasil lembar observasi pada siklus I diperoleh rata-rata persentase pelaksanaan kegiatan pembelajaran responden guru mencapai 65.38% dan hasil rata-rata persentase angket kualitas pembelajaran mencapai 61.82% dan dikategorikan cukup. Pada siklus II diperoleh rata-rata persentase pelaksanaan kegiatan pembelajaran responden guru mencapai 81.73% dan hasil rata-rata persentase angket kualitas pembelajaran mencapai 79.65% dan dikategorikan baik. Kata Kunci: example non example, media gambar